GEOCHRONOLOGY AND GENESIS OF SUBALKALINE BASALTIC LAVA RIVERS AT THE DZHAVAKHETI HIGHLAND, LESSER CAUCASUS: K-AR AND SR-ND ISOTOPIC DATA - Lebedev V.A.; Bubnov S.N.; Chernyshev I.V.; Chugaev A.V.; Dudauri O.Z.; Vashakidze G.T. (My University, 2007)
The paper reports newly obtained K-Ar isotopic-geochronological data on the age of three lava flows (Khrami, Mashavera, and Kura), which begin at the Javakheti volcanic highland in southern Georgia. All of the dated rocks, including those from the Kura Flow, which was previously considered as the Pleistocene, are demonstrated to have a Pliocene age. The lavas of the longest Khrami Flow were erupted at 3.25–3.10 Ma, and those of the Kura and Mashavera Flows at 2.20–2.05 Ma, a fact testifying to two pulses of volcanic activity at the Javakheti Highland. The petrogeochemical and isotopic characteristics of the rocks (87Sr/86Sr = 0.7039–0.7042; ∈Nd = 3.4–5.1) indicate that they are subalkaline within-plate basalts formed by the fractional crystallization of a basic mantle melt with the usually discontinuous selective or rarely continuous contamination with material that was not in geochemical equilibrium with the melt. The volcanics of the Khrami Flow are characterized by the less radiogenic Sr isotopic composition and the highest ∈Nd values, while the younger rocks of the Mashavera and Kura Flows have similar and more “crustal” isotopic signatures. The 87Sr/86Sr ratios of the Javakheti subalkaline basalts are close to the initial Sr isotopic ratios of the Quaternary and Middle Pliocene dacite lavas from the same territory. Considered together with petrogeochemical and geological data, this suggests that all young rocks in Southern Georgia were produced in similar tectonic and geodynamic environments.
Keywords: Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен